Vacuum electron beam deposition of carbide steels: Part 3. Effect of the number of passes on the structure and phase condition of composite coatings based on R6M5 high-speed steel; Welding International; Vol. 25, iss. 2 - Gnyusov S. F. Sergey Fedorovich; Ignatov A. A.; Tolmachev K. A.; Durakov V. G. (2011, 2011)
Title screen